APPLICATION OF CLIL IN HIGHER EDUCATION AND ITS IMPACT ON ACADEMIC ENGLISH COMPETENCE: A SYNTHESIS OF MODELS, EVIDENCE, AND IMPLEMENTATION CONDITIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Content and Language Integrated Learning (CLIL) in higher education refers to teaching and learning disciplinary content through an additional language (often English), while also pursuing explicit language-development goals. In practical university settings, CLIL frequently overlaps with English-Medium Instruction (EMI), but the defining feature of CLIL is its dual focus: language development is not treated as an accidental by-product; it is deliberately designed into content teaching. This “dual-focused educational approach” is consistently emphasized in CLIL-oriented literature and higher-education CLIL discussions.The rationale for CLIL is especially compelling when the target is academic English competence rather than everyday conversational ability. Academic competence entails discipline-specific vocabulary, academic discourse functions (defining, describing processes, comparing, hypothesizing, arguing from evidence), and the ability to participate in academic interaction (asking for clarification, presenting claims, defending positions). The CLIL premise is that sustained exposure to content tasks, delivered in English, creates authentic pressure to use these academic functions repeatedly, which should accelerate academic language development.